Factors That Influence Purchasing Decisions On Brazilian Grapes AT CV. Gentar Brazilian Grapes Teja Village, Rajagaluh Sub-District, Majalengka District - Sri Muriyanti; Elisa Yulistiani; Evi Noviyanti; Siti Wahana; Dina Dwirayani (Agricultural Science, 2025)
The purpose of this study was to analyze the factors that influence purchasing decisions for Brazil grapes at CV. Gentar Brazil Wine, Majalengka. A quantitative approach was used with a survey method of 100 respondents. The independent variables are price, product quality, promotion, and location, while the dependent variable is the purchase decision. Data analysis was carried out using multiple linear regression. The results showed that the four variables had a significant effect on purchasing decisions, with an R² value of 71.5%. Only product quality and location have a significant effect partially, while price and promotion do not. Product quality is the dominant factor influencing purchasing decisions, and strategic location. These results indicate the importance of improving product quality and distribution access in Brazil grape marketing strategies. This research can be expected to be a reference for the development of exotic horticultural agribusiness at the local level